Application of Wind as a Renewable Energy Source for Passive Cooling through Windcatchers Integrated with Wing Walls - Payam Nejat; Fatemeh Jomehzadeh; Hasanen Mohammed Hussen; John Kaiser Calautit; Muhd Zaimi Abd Majid (Energies, 2018)
Generally, two-third of a building’s energy is consumed by heating, ventilation and air-conditioning systems. One green alternative for conventional air conditioner systems is the implementation of passive cooling. Wing walls and windcatchers are two prominent passive cooling techniques which use wind as a renewable resource for cooling. However, in low wind speed regions and climates, the utilization of natural ventilation systems is accompanied by serious uncertainties. The performance of ventilation systems can be potentially enhanced by integrating windcatchers with wing walls. Since previous studies have not considered this integration, in the first part of this research the effect of this integration on the ventilation performance was assessed and the optimum angle was revealed. However, there is still gap of this combination; thus, in the second part, the impact of wing wall length on the indoor air quality factors was evaluated. This research implemented a Computational Fluid Dynamics (CFD) method to address the gap. The CFD simulation was successfully validated with experimental data from wind tunnel tests related to the previous part. Ten different lengths from 10 cm to 100 cm were analyzed and it was found that the increase in wing wall length leads to a gradual reduction in ventilation performance. Hence, the length does not have a considerable influence on the indoor air quality factors. However, the best performance was seen in 10 cm, that could provide 0.8 m/s for supply air velocity, 790 L/s for air flow rate, 39.5 1/h for air change rate, 107 s for mean age of air and 92% for air change effectiveness.